An assessment of road and bridge construction in Simen and Begemider province, 1963-1991 - Derso, Tesfamichael Fentie (Ethiopian Journal of Social Sciences, 2023)
Due to different factors the academic literature places less emphasis on road and bridge construction in Ethiopia. The main objective of this study is to deal with the history of road and bridge construction and their significance for the people of Simen and Begemider province during the monarchy and the Derg regime. The monarchical period was crucial in that old structures were repaired and construction of new ones commenced.  The Derg also constructed many roads and bridges and its rule was considered a golden age in this regard. The study employs a qualitative research method in the sense that primary and secondary sources were exhaustively exploited. Data were collected from key informants who provided relevant information about the issue under investigation through semi-structured interviews. The data collected from informants were cross-checked with abundant archival sources, which were gathered from Central Gondar Archival Center (CGAZA) existing in the form of photographs, design plans and manuscripts. The study identified many roads and bridges that were constructed during the study period. Moreover, the Tekeze River Bridge and many other bridges had been constructed since the restoration of the monarchy in 1941. After it assumed power in 1975, the Derg undertook repair works on the early bridges and began the construction of new ones by giving much attention to road construction. As a result, these roads and bridges played important roles in the socio-economic and political life of the people in the study area and beyond.